Oral and cephalometric characteristics of hypohidrotic ectodermal dysplasia: Case report - Sánchez-Tito, Marco A. (Revista Estomatológica Herediana, 2022)
Hypohydrotic ectodermal dysplasia (HED) is a genetic disorder that affects the development of ectodermal tissues. This study reports a case of a 5-year-old male patient, with clinical extra and intraoral characteristics of HED. The intraoral clinical examination revealed a generalized absence of teeth, panoramic radiograph revealed the presence of permanent first molars with taurodontism, and confirm the oligodontia. Cephalometric analysis revealed a class III skeletal relationship, due to deficiency in the sagittal development of the maxilla and an anti-clockwise growth tendency. Alterations in craniofacial development require multidisciplinary treatment and long-term follow-up to monitor craniofacial growth.